Nurse's pocket guide : diagnoses, prioritized interventions, and rationales - Doenges, Marilynn E., 1922-; Moorhouse, Mary Frances, 1947-; Murr, Alice C., 1946- (Philadelphia, PA : F.A. Davis Company, 2022)
The perfect pocket guide makes care planning easier. This quick-reference tool has exactly what you need to select the appropriate diagnoses to plan your patients' care effectively. The 16th Edition features all the latest nursing diagnoses and updated interventions from NANDA-I 2021-2023.
Chapter 1: The Nursing Process and Planning Client Care -- Chapter 2: Nursing Diagnoses in Alphabetical Order -- Chapter 3: Health Conditions and Client Concerns With Associated Nursing Diagnoses.
Description based upon print version of record.
Includes index.
WorldCat record variable field(s) change: 050, 082, 650
Keywords: Nursing diagnosis -- Handbooks, manuals, etc; Nursing care plans -- Handbooks, manuals, etc; Handbooks and manuals; Electronic books